Dynamic Contrast-enhanced Magnetic Resonance Imaging Evaluation of Whole Tumour Perfusion Heterogeneity Predicts Distant Disease-free Survival in Locally Advanced Rectal Cancer. Issue 9 (September 2022) - Pham, T.T.; Wong, K.; Liney, G.; Lim, S.; Graham, P.L.; Borok, N.; Truong, M.X.; Rai, R.; Henderson, C.; Lee, M.; Barton, M.B.
Abstract: Aims: To evaluate diffusion-weighted imaging and dynamic contrast-enhanced magnetic resonance imaging for the prediction of disease-free survival (DFS) in patients with locally advanced rectal cancer. Materials and methods: Patients with stage II or III rectal adenocarcinoma undergoing neoadjuvant chemoradiotherapy (CRT) and surgery were eligible. Patients underwent multi-parametric magnetic resonance imaging (diffusion-weighted imaging and dynamic contrast-enhanced) before CRT, during CRT (week 3) and after CRT (1 week prior to surgery). Whole tumour apparent diffusion coefficient (ADC) and K trans histogram quantiles (10th, 25th, 50th, 75th, 90th) were extracted for analysis. The associations between ADC and K trans at three timepoints with time to relapse were analysed as a continuous variable using a Cox proportional hazard model. Results: Thirty-three patients were included in this analysis. The median follow-up was 4.4 years. No patient had locoregional relapse. Nine patients developed distant metastases. The hazard ratios for after CRT K trans 10th ( P = 0.035), 25th ( P = 0.048), 50th ( P = 0.046) and 75th ( P = 0.045) quantiles were statistically significant for DFS. The best K trans cut-off point after CRT for predicting relapse was 28 × 10 −3 mL/g/min (10th quantile), with a higher K trans value predicting distant relapse. The 4-year DFS probability was 0.93 for patients with after CRT K trans value ≤28 × 10 −3 mL/g/min versus 0.45 for patients with after CRT K trans value >28 × 10 −3 mL/g/min. ADC was not able to predict DFS. Conclusions: Patients with higher K trans values after CRT (before surgery) in a histogram analysis of whole tumour heterogeneity had a significantly lower 4-year distant DFS and could be considered for more intense systemic therapy. Highlights: DCE-MRI is predictive of 4-year disease-free survival in rectal cancer. Patients with higher K trans after chemoradiotherapy had higher distant relapse risk. DWI-MRI was unable to predict disease-free survival in rectal cancer.